(untitled) (Research, Society and Development, 2026)
Schools that bring together students of different ages and grade levels in the same classroom are part of the reality of Brazilian education, as are multi-grade classes. Therefore, the general objective of this study is to analyze the training of teachers and pedagogical management of multi-grade classes in rural education. Specific objectives: to highlight continuing education for teachers of multi-grade classes; to show the difficulties faced by teachers of multi-grade classes; to verify the new strategies and methodologies used by teachers in multi-grade classes. Methodology: this is a qualitative bibliographic study. Regarding teacher training, it is observed that the training project should prioritize collective reflection on practice, values, and knowledge built through experience, so that teachers can transcend the walls of the school space. Thus, with qualified teachers, the rural population can demonstrate their knowledge, whose identity will be seen by society as that of subjects who construct their own histories with the help of the teacher. In short, the great challenge of multi-grade classrooms lies in the difficulty faced by teachers and students in achieving the teaching-learning process throughout the activities and the school year. Thus, the constant search for improved pedagogical activity proposals facilitates and assists the teacher’s work, as well as the students’ learning.